Effects of whey protein isolate on body composition, lipids, insulin and glucose in overweight and obese individuals - Pal, Sebely; Ellis, Vanessa; Dhaliwal, Satvinder (British journal of nutrition, 2010)
The health benefits currently associated with increased dairy intake may be attributable to the whey component of dairy proteins. The present study evaluated the effects of whey protein supplementation on body composition, lipids, insulin and glucose in comparison to casein and glucose (control) supplementation in overweight/obese individuals for 12 weeks. The subjects were randomised to whey protein, casein or glucose supplementation for 12 weeks according to a parallel design. Fasting blood samples and dual-energy X-ray absorptiometry measurements were taken. Seventy men and women with a mean age of 48·4 (sem 0·86) years and a mean BMI of 31·3 (sem 0·8) kg/m2 completed the study. Subjects supplemented with whey protein had no significant change in body composition or serum glucose at 12 weeks compared with the control or casein group. Fasting TAG levels were significantly lowered in the whey group compared with the control group at 6 weeks (P = 0·025) and 12 weeks (P = 0·035). There was a significant decrease in total cholesterol and LDL cholesterol at week 12 in the whey group compared with the casein (P = 0·026 and 0·045, respectively) and control groups (P < 0·001 and 0·003, respectively). Fasting insulin levels and homeostasis model assessment of insulin resistance scores were also significantly decreased in the whey group compared with the control group (P = 0·049 and P = 0·034, respectively). The present study demonstrated that supplementation with whey proteins improves fasting lipids and insulin levels in overweight and obese individuals.